Developing Conservation Horticulture and Conserving Threatened Hibiscus Species in the Asia-Pacific Islands Region - Wawan Sujarwo; Jean Linsky; Lex Thomson (Badan Penelitian dan Pengembangan Provinsi Papua Barat, 2020)
The objective of this study is to ensure the conservation of iconic Hibiscus species in the Asia-Pacific Islands region though collaborative action. Almost all of the 23 species of Hibiscus in section Lilibiscus are rare and restricted or critically endangered in nature. The study focussed on establishing the status of horticulturally important and newly discovered Hibiscus species in Indonesian New Guinea and Vanuatu through field surveys. The species have been conserved in ex situ conservation collections and capacity has been built within local partners to collect, propagate and conserve Hibiscus species. Field surveys and ex situ conservation activities will inform the development of conservation action plans for Indonesian and Pacific Islands Hibiscus species by regional stakeholders.